Economic significance of bees in Polish fruit-growing - Majewski, Janusz; Pizło, Wojciech (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2012)
Bees and other insects play a significant role in the fertilization of entomophilous plants in our climatic zone. Many species of cultivated plants are accounted for by entomophilous plants. The most important among them are: rape and turnip, buckwheat, orchard plants, fruit-bearing shrubs and perennial plantations. This attests to the significant role of insects in agriculture. In fruit-growing fertilizer insects are a factor decisive for the gathered crop. This shows that fruit growers ought to make use of fertilizer insects. In the surveyed group of fruit-growing farms located near Warka and Grójec only 10% owned or hired fertilizer insects. The remaining farms made no use of such services, which was probably due to the lack of knowledge about the role of insects in the pollination of orchards. Another explanation of this situation could be the condition of the natural environment and the sufficient number of wild fertilizers.
Keywords: bees; orchards; pollination; effects of pollination